Warum ist das „Philosophieren mit Kindern“ an Grundschulen und insbesondere für den Sachunterricht sinnvoll? - Schmiljun, Iga Maria; Schmiljun, André (Filozofia Publiczna i Edukacja Demokratyczna, 2019)
Philosophizing with children is a valuable integrative method that should be practiced at primary schools, especially within the education of social sciences and technology. Children are confronted with existential questions that they learn to discuss and approach from different perspectives. Additionally, this method helps to foster children’s moral and cognitive skills and competences.